Guide and advances on childhood obesity determinants: Setting the research agenda. (4th November 2021) - Tur, Josep A.; Martinez, J. Alfredo
Summary: Childhood obesity demands global solutions. Low birth weight and small for gestational age were associated with childhood obesity. Available data do not support prenatal exposure to antibiotics as risk factor for childhood obesity, and posology must be assessed. Prenatal exposure to persistent organic pollutants shows associations with childhood obesity. Gut microbiota composition influences obesity onset in childhood. Despite the unquestionable role of Mediterranean diet on healthy weight, there are only incomplete indications of metabolic benefits in childhood weight after following Mediterranean diet. Negative association between total dairy consumption and childhood obesity has been found, but inverse causality could not be discarded. Ultra‐processed food intake is an adverse determinant of childhood obesity. Physical inactivity and sedentarism are critical risk factors of children adiposity; hence, built environment and environmental features will be determinants of childhood obesity. A consistent metabolic pattern of childhood obesity was observed; metabolomics research is needed to assess the role of specific molecules concerning childhood obesity. Epigenetic experiences support association with childhood obesity for DNA methylation of specific genes and miRNAs. Therefore, recent childhood obesity rates cannot only be explained by genetic predisposition and changes in lifestyle habits. It implies gene–environment interactions. It will be the next research.